Does the DVR(®) plate restore bony anatomy following distal radius fractures? - Patel, S (Ann R Coll Surg Engl, 2014)
INTRODUCTION: Fractures of the distal radius are common. Malreduced fractures are associated with residual functional deficiency. There has been a trend over the last few years for using fixed angle volar locking plates to surgically stabilise this injury. Our unit uses the DVR(®) plate (DePuy, Warsaw, IN, US). Nevertheless, it is unknown whether the normal bony anatomy is recreated or merely restored to acceptable limits with its usage. The aim of this study was to evaluate the reduction achieved compared with an uninjured population and pre-existing quoted ‘normal’ values. Furthermore, we wanted to identify the percentage of cases that were reduced to acceptable limits, and determine whether the grade of the surgeon and fracture type was a confounding influence on this reduction. METHODS: A retrospective review of the 3-month postoperative radiography of 48 eligible patients who underwent open reduction and internal fixation of a distal radius fracture with a DVR(®) plate was undertaken. RESULTS: Volar tilt, radial length and inclination were different to quoted normal values (p<0.01). Despite this, these parameters fell within acceptable limits in 46 cases; this was not influenced by fracture type or grade of operating surgeon. CONCLUSIONS: The DVR(®) plate restores the bony anatomy to within acceptable limits in the majority of patients who have sustained a fracture of the distal radius although of all parameters investigated, the widest variability is seen in volar tilt.